Решите уравнение: 1) (х+5)^2-(х-1)^2=48 2) (2х-3)^2+(3-4х)(х+5)=82 

Решите уравнение: 1) (х+5)^2-(х-1)^2=48 2) (2х-3)^2+(3-4х)(х+5)=82 
Гость
Ответ(ы) на вопрос:
Гость
(х+5-х+1)(x+5+x-1)=48 6(2x+4)=48 2x+4=8 2x=4 x=2 2) (2x-3)^2+(3x+15-4x^2-20x)=82 (2x-3)^2-4x^2+17x+15=82 4x^2-12x+9-4x^2+17x+15=82 5x+26=82 5x=56 x=11.2
Гость
1) (х+5)^2-(х-1)^2=48 x^2+10x+25-x^2+2x-1-48=0 12x-24=0 x=24/12 x=2   2) (2х-3)^2+(3-4х)(х+5)=82  4x^2-12x+9-17x+15-4x^2-82=0 -29x-58=0 x=-58/29 x=-2
Не нашли ответ?
Ответить на вопрос
Похожие вопросы